A combination of anti‐PD‐L1 mAb plus Lm‐LLO‐E6 vaccine efficiently suppresses tumor growth and metastasis in HPV‐infected cancers. (9th August 2017) - Lin, Po‐Lin; Cheng, Ya‐Min; Wu, De‐Wei; Huang, Yu‐Ju; Lin, Hun‐Chi; Chen, Chih‐Yi; Lee, Huei
Abstract: PD‐1/PD‐L1 immunotherapy is viewed as having clinical benefits in advanced cancers but is effective in only a few patients, suggesting that an efficient combination approach is needed to improve efficacy. Immunohistochemistry analysis indicated that PD‐L1 expression was correlated with the E6 expression in tumors from 122 lung cancer patients. The poorest survival occurred in PD‐L1‐positive/E6‐positive tumor. PD‐L1 expression was increased by the expression of E6, but not the E7, oncoprotein in lung and cervical cancer cells. PD‐L1 expression was responsible for E6‐mediated colony formation and soft agar growth. Therefore, PD‐L1 secreted from tumor cells may directly promote tumor progression, particularly in E6‐positive tumors. Immune deficiency nude mice were used to test the possibility that combining anti‐PD‐L1 mAb with Lm‐LLO‐E6 vaccine could have a higher antitumor activity compared with anti‐PD‐L1 mAb or Lm‐LLO‐E6 vaccine alone. A greater antitumor activity was obtained with anti‐PD‐L1 mAb + Lm‐LLO‐E6 vaccine than with anti‐PD‐L1 mAb or Lm‐LLO‐E6 alone in subcutaneous and metastatic tumors induced by TL‐1 and SiHa cells. The longest survival time for nude mice was observed in the anti‐PD‐L1 mAb + Lm‐LLO‐E6 vaccine group. In conclusion, an anti‐PD‐L1 mAb + Lm‐LLO‐E6 vaccine may be an efficient treatment for suppression of tumor growth and metastasis induced by HPV‐infected cells. Abstract : We have provided evidence that an anti‐PD‐L1 mAb + Lm‐LLO‐E6 vaccine combination is an efficient therapeutic approach against HPV‐infected NSCLC. In addition, the anti‐PD‐L1 mAb + Lm‐LLO‐E6 vaccine combination also efficiently suppresses SiHa cell‐induced tumors in nude mice. Therefore, we suggest that anti‐PD‐L1 mAb + Lm‐LLO‐E6 vaccine combination therapy may have a greater clinical benefit than anti‐PD‐L1 or HPV DNA vaccine immunotherapy in cancer patients with HPV‐infected tumors.